Synovial Fluid Proteomics From Serial Aspirations of ACL-Injured Knees Identifies Candidate Biomarkers. Issue 7 (June 2023) - Rai, Muhammad Farooq; Cai, Lei; Zhang, Qiang; Townsend, R. Reid; Brophy, Robert H.
Background: Anterior cruciate ligament (ACL) tears often result in knee effusion and an increased risk for developing knee osteoarthritis (OA) in the long run. The molecular profile of these effusions could be informative regarding initial steps in the development of posttraumatic OA after an ACL tear. Hypothesis: The proteomics of knee synovial fluid changes over time after ACL injury. Study Design: Descriptive laboratory study. Methods: Synovial fluid was collected from patients with an acute traumatic ACL tear presenting to the office for evaluation (18.31 ± 19.07 days from injury) (aspiration 1) and again at the time of surgery (35.41 ± 58.15 days after aspiration 1 (aspiration 2). High-resolution liquid chromatography mass spectrometry was used to assess the quantitative protein profile of synovial fluid, and differences in protein profile between the 2 aspirations were determined computationally. Results: A total of 58 synovial fluid samples collected from 29 patients (12 male, 17 female; 12 isolated ACL tear, 17 combined ACL and meniscal tear) with a mean age and body mass index of 27.01 ± 12.78 years and 26.30 ± 4.93, respectively, underwent unbiased proteomics analysis. The levels of 130 proteins in the synovial fluid changed over time (87 high, 43 low). Proteins of interest that were significantly higher in aspiration 2 included CRIP1, S100A11, PLS3, POSTN, and VIM, which represent catabolic/inflammatory activities in the joint. Proteins with a known role in chondroprotection and joint homeostasis such as CHI3L2 (YKL-39), TNFAIP6/TSG6, DEFA1, SPP1, and CILP were lower in aspiration 2. Conclusion: Synovial fluid from knees with ACL tears exhibits an increased burden of inflammatory (catabolic) proteins relevant to OA with reduced levels of chondroprotective (anabolic) proteins. Clinical Relevance: This study identified a set of novel proteins that provide new biological insights into the aftermath of ACL tears. Elevated inflammation and decreased chondroprotection could represent initial disruption of homeostasis, potentially initiating the development of OA. Longitudinal follow-up and mechanistic studies are necessary to assess the functional role of these proteins in the joint. Ultimately, these investigations could lead to better approaches to predict and possibly improve patient outcomes.